Pemikiran dan Praktik Kepemimpinan Sunan Gunung Jati Serta Relevansinya bagi Kepemimpinan Pendidikan Islam Kontemporer - Azwar Abdurakhman; Saepul Hidayat; Shovi Sholahiyah Humairo; Muhammad Kosasih; Ika Kartika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This article aims to comprehensively analyze the leadership thoughts and practices of Sunan Gunung Jati, a central figure in the Walisongo (Nine Saints) and reconstruct their relevance for the development of contemporary Islamic educational leadership. This research employs a qualitative approach with library research, examining primary sources in the form of Cirebon historical manuscripts and secondary sources in the form of scholarly books and reputable journal articles. The analysis utilizes historical, conceptual, and contextual approaches to uncover the leadership values ​​embodied in Sunan Gunung Jati's socio-religious practices. The results indicate that Sunan Gunung Jati's leadership is characterized by the integration of spiritual, cultural, and structural values, manifested through exemplary behavior (uswah hasanah), trustworthiness, deliberation (shura), justice, and an orientation toward social transformation. These values ​​are strongly relevant in the development of a contemporary Islamic educational leadership model oriented toward character formation, strengthening institutional culture, integrating modern management with Islamic spirituality, and developing a sustainable educational civilization.